Air temperature, humidity and dew point measurements during the BONUS INTEGRAL WINTER cruise on RV Aranda (2019-02-28 - 2019-03-11) - Milla Johansson; Heidi Pettersson; Kimmo Tikka (PANGAEA, 2021)
The data set consist of navigation and automatic weather station data from BONUS INTEGRAL WINTER cruise on RV Aranda for monitoring the green-house gases and related parameters 28.02.-11.03.2019. The cruise was one of the two research cruises made within the BONUS INTEGRAL project (2017-2020): https://www.io-warnemuende.de/integral-home.html and https://www.bonusportal.org/projects/blue_baltic_2017-2020/integral